2011
DOI: 10.1159/000328635
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Risk of High-Grade Bladder Cancer Using Noninvasive Data

Abstract: Aim: To examine the hypothesis that the risk of high-grade bladder cancer can be predicted using noninvasively obtained data. Patients and Methods: We retrospectively analyzed the database of 431 patients that had transurethral resection of first-time bladder tumors between June 1998 and December 2009. Pre-operative parameters evaluated were: patients’ age; gender; sonographic tumor diameter, number and location of tumor inside the bladder; presence of hydronephrosis, and results of urinary cytology. Parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Data of 1062 patients, all treated with BCG, were used to identify risk factors for recurrence and progression after BCG treatment. Several other prediction models have been developed for NMIBC [ 9 15 ], but none of them included solely patients who, according to the guidelines, should have been and in fact were treated with intravesical chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Data of 1062 patients, all treated with BCG, were used to identify risk factors for recurrence and progression after BCG treatment. Several other prediction models have been developed for NMIBC [ 9 15 ], but none of them included solely patients who, according to the guidelines, should have been and in fact were treated with intravesical chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Risk of cancer-specific mortality following RC for MIBC is usually determined by pathological tumour stage and lymph node status. Since cancer-specific survival (CSS) rates vary widely, other prognostic factors have been evaluated [5,6]. …”
Section: Introductionmentioning
confidence: 99%
“…In addition, a recent study conducted by Shapur et al. [ 21 ] revealed that advancing age is a significant risk factor for HG BCa ( p <0.0001, OR: 1.05; 95% CI: 1.03–1.06). Subsequently, we revealed that older patients might be more likely with HG tumour (OR: 1.041; 95% CI: 1.005–1.078; p =0.025) ( Supplementary Table 3 ).…”
Section: Discussionmentioning
confidence: 99%